2015
DOI: 10.1186/s12866-015-0434-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility profile of listeria species from ready-to-eat foods of animal origin in Gondar Town, Ethiopia

Abstract: BackgroundListeriosis, mostly caused by Listeria monocytogenes species, has become a major concern to public health authorities due to its clinical severity and high mortality rate, particularly in high risk groups. Currently, there is limited information regarding the prevalence and antimicrobial susceptibility profiles of listeria species in ready-to-eat foods of animal origin in Gondar town, Ethiopia. The aim of this study was to determine the prevalence and antimicrobial susceptibility pattern of Listeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
82
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(126 citation statements)
references
References 20 publications
25
82
8
Order By: Relevance
“…Ready-to-eat foods play a crucial role in the transmission of listeriosis to humans. A study carried out with 384 food samples in Ethiopia showed a 25% prevalence of L. monocytogenes among which some isolates were multi-drug resistant (penicillin, nalidixic acid, tetracycline and chloramphenicol) emphasizing the need for adopting hygienic practices in food processing industries (Garedew et al 2015). Disease can also spread through carrier animals and rodents.…”
Section: Epidemiology Transmission and Spreadmentioning
confidence: 99%
“…Ready-to-eat foods play a crucial role in the transmission of listeriosis to humans. A study carried out with 384 food samples in Ethiopia showed a 25% prevalence of L. monocytogenes among which some isolates were multi-drug resistant (penicillin, nalidixic acid, tetracycline and chloramphenicol) emphasizing the need for adopting hygienic practices in food processing industries (Garedew et al 2015). Disease can also spread through carrier animals and rodents.…”
Section: Epidemiology Transmission and Spreadmentioning
confidence: 99%
“…Garedew et al. () found that 16 (66.7%), 12 (50%), 9 (37.5%), and 4 (16.6%) isolates of 24 L. monocytogenes isolates from RTE foods of animal origin exhibited resistance for penicillin, nalidixic acid, tetracycline, and chloramphenicol, respectively. Further, four (16.7%) were multidrug‐resistant isolates.…”
Section: Prevalence Of Antibiotic Resistance Among Food Isolates Of Lmentioning
confidence: 99%
“…Study conducted by Seyoum et al (2015) showed that prevalence of Listeria species was 28.4% and specifically that of L. monocytogenes was 5.6% from raw bovine milk and milk products from central highlands of Ethiopia. Other study conducted in Gondar on foods of animal origin indicated that 25% were positive for Listeria species and that of L. monocytogenes was 6.25% (Garedew et al, 2015) …”
Section: Listeriosismentioning
confidence: 99%